Rancang dan Bangun Website Aplikasi Perhitungan Pajak Tukin Progresif di Kemendikbud Menggunakan Metode Extreme Programing - Anggun Fergina; Indra Yustiana; M Azri Riyandi (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
This study discusses the design and development of a website for calculating progressive income tax on Performance Allowance (Tukin) in the Ministry of Education and Culture (Kemendikbud). There are often issues in the manual calculation process of Tukin tax, resulting in errors and consuming a lot of time. To overcome these problems, this research proposes the use of a website that can perform fast and accurate calculations. The utilization of information technology in this process provides various benefits, including improving efficiency, facilitating access, and ensuring transparency in tax calculations. With this website, employees can understand and calculate their taxes more effectively and accurately. In this research, the development method known as Extreme Programming was used. The programming language used was PHP, while Bootstrap and CodeIgniter were used as frameworks. The implementation carried out in this research demonstrates how the appropriate technology and development methods can simplify the tax calculation process and improve accuracy. The result of this research is a well-functioning website for calculating progressive Tukin tax. The website was also tested using black box method with various conditions, and the results met the desired expectations. Therefore, it is expected that this website can be widely used and help improve the overall Tukin tax calculation process in Kemendikbud, significantly enhancing efficiency and accuracy